Analisis Manajemen Modal Kerja dan Inovasi Produk Terhadap Profitabilitas Untuk Mengembangkan UMKM Kerupuk Hj. Mutmainnah di Dakiring Kecamatan Socah Kabupaten Bangkalan - Fifin, Fifin; purnamawati, Purnamawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
Management of working capital management is very important for the smooth running of a business, in addition to managing finances, good working capital management will also help MSMEs in obtaining profits. Working capital is a company's investment both in the form of cash, securities, receivables and inventories minus current liabilities which will be used to finance current assets.The method used is a quantitative descriptive, by conducting interviews and direct observation of UMKM owners. The purpose of this study is to determine working capital management at Hj. Mutmainnah in Dakiring, Socah District, Bangkalan Regency, and to find out whether product innovation can increase the profitability of UMKM.            Working capital management in this study was measured using cash budget calculations, EOQ before innovation was 253 kg, and when product innovation was 260 kg it increased by 47%, Savety Stock before innovation was 38 units and when product innovation was 42 units so has increased by 76%, Lead time before product innovation is 15 days and if product innovation is 17 days, Reorder Point before product innovation is 53 days and when product innovation is 60 days, As well as inventory turnover ratio which can be compared with the results before carrying out product innovations 24 rounds and when carrying out product innovations 29 times rounds so that there is an increase of 64%. Product innovation is carried out by adding flavor to the crackers and adding labels to the cracker packaging, so that they can be marketed through online media, super markets and souvenir centers in Bangkalan, Madura. Based on the results of the research, the existence of this product innovation will have a good influence on MSMEs even though with increased working capital and costs in the cracker business, profits from sales have also increased significantly by 84% from the previous year.